An Evaluation of the Initial Impact of the Medical Assistance Program for the Poor in Georgia - Hou, Xiaohui (World Bank, Washington, DC, 2012)
As part of the recent health reform effort, the government of Georgia launched a Medical Assistance Program in June 2006 to provide health insurance to its poor population. So far the program covers slightly over 50 percent of the poor and provides benefit coverage for outpatient and inpatient care. This paper estimates initial impact of the Medical Assistance Program and assesses whether the benefits have reached the poorest among those eligible, using utilization data from June 2006 to December 2006. Based on the analysis using a regression discontinuity design and a three-part model, the paper presents two main findings. First, the Medical Assistance Program has significantly increased utilization of acute surgeries/inpatient services by the poor. Second, the benefits have successfully reached the poorest among the poor. These two findings indicate that government efforts to improve the poor's access to and utilization of health services are yielding results. The paper emphasizes that the initial dramatic increase in surgeries must be interpreted with caution, given the possible misclassification or misreporting of acute surgeries in the data. The paper also stresses the need to continue monitoring implementation of the Medical Assistance Program and further improve program design, particularly the targeting mechanism, to achieve better efficiency, effectiveness and overall equity in access to health care services.